Menthol-loaded PLGA Micro and Nanospheres: Synthesis, Characterization and Degradation in Artificial Saliva - Holz,Juliana Pelisoli (2018)
Menthol-loaded PLGA micro/nanospheres were synthesized using the multiple emulsion/solvent evaporation technique. Parameters such as stirring rate, external surfactant content, PLGA/menthol weight ratio, solvent evaporation and lyophilization time were evaluated as well as the degradation of micro/nanospheres in an artificial saliva medium. The menthol/PLGA micro/nanospheres thus obtained had a size distribution of between 217 nm and 13 µm and particles with spherical and dense morphology were evidenced by SEM micrographs. FTIR and TGA data showed an increase up to 60% of menthol incorporated in the micro/nanoparticles. The degradation of menthol-loaded PLGA micro/nanoparticles in artificial saliva significantly affected the particles morphology and appears to be an effective medium for releasing menthol.